FRAMING OF SENTENCE COMPLEXITY IN EDITORIAL NEWS: CASE STUDY IN “THE JAKARTA POST AND KOMPAS - Syahrul Efendi Lubis; Zainuddin Zainuddin (JALC : JOURNAL OF APPLIED LINGUISTIC AND STUDIES OF CULTURAL, 2023)
This research is about Framing of Sentence Complexity in Editorial News: A Case Study in “The Jakarta Post and Kompas” using the topic of "Health". The problems in this study are: what is the level of complexity of sentences in “The Jakarta Post” newspaper in the form of editorial news, what is the level of complexity of sentences in “Kompas” newspaper in the form of editorial news and how is the comparison of the level of complexity of sentences in “The Jakarta Post and Kompas” newspapers in the form of editorial news. The research method used is qualitative with a case study design. The data sources used are newspapers from “The Jakarta Post and Kompas”. It was concluded that the results of research on the level of complexity of sentences in “The Jakarta Post and Kompas” newspapers in the form of news editorials about "Health", simple sentences and compound sentences often appear in the construction of complex sentences. This is because the two newspapers avoid sentences that are too long so that they can minimize the wastage of words in sentences and can provide information to readers by using appropriate conjunctions. The more concise the presentation of language and sentences in newspapers, the easier it will be for readers to get information.